Kalpatharu: A plant with virtues - R, Raghavendra H; Desai, Chirag; Hiremath, Varun M; K, Tejukumar B; V, Udaya T (Indian Horticulture, 2021)
The concept of waste valorisation has been precisely defined as the process of converting waste materials into useful products. Waste valorisation relies on the assumption that even after efficient intended use, the waste still contains untapped sources that can be converted into other useful forms. Apart from the development of technologies, waste valorisation has several advantages like, reduction of volume of produce, recovery of more space and mainly amelioration of environmental pollution. As banana fruit is considered, it is the cheapest, plentiful and most nutrient fruit which is having great economic significancy in our country. In India it is so predominant crop and popular among people that it is liked by both poor and rich alike. It is an important source of fibre, fodder, food, beverages, fermented sugars, medicines, flavourings, silage, rope, cordage, garlands, shelter, clothing, making house roofs and wall linings. By considering all these multifaceted uses, it is referred to as Kalpatharu. The banana industry produces a large volume of waste which is neglected and left to decompose in an uncontrolled way. Hence the application of valorisation would save hindrances to the industrial development.